Kewajiban Nafkah suami menurut hukum Islam dan implikasinya terhadap stabilitas keluarga - Kamaliya, Firda Faroh (Maliki Interdisciplinary Journal, 2024)
Since 2019 until now, divorce has occurred very frequently and the cause is mostly due to lack of income. This research aims to provide an explanation and understanding of the concept of husband's maintenance obligations according to Islamic law, as well as the role of maintenance in maintaining household stability. The type of research used in this research is normative juridical, namely legal research carried out using secondary data. The approach used is conceptual. The results of this research show that maintenance is a husband's third obligation after the husband provides a dowry and acts fairly towards his wife. The support provided is in the form of income, such as food, drink, shelter, and so on. Apart from physical support, a husband must also provide mental support such as loving, providing protection for his wife and so on. Providing physical and spiritual support in a family is the obligation of husband and wife because a good family is a family that complements each other. A living is very important to maintain household stability, because providing a good and sufficient living will create and give rise to happiness in the family.